Application of The Unified Theory of Acceptance and Use of Technology Method to Analyze Factors Influencing The Use of Digital Wallets in Indonesia - Edhie Rachmad, Yoesoep; Ady Bakri, Asri; Nuraini, Rini; Widia Nurdiani, Tanti; Kushariyadi (Jurnal Informasi dan Teknologi, 2024)
This study aims to determine how the intention to use digital wallets is influenced by performance expectancy, effort expectancy, social influence, and enabling factors. The author selected the type of conclusive research design for this study. Descriptive research is the methodology, and a cross-sectional design is employed to collect data. Questionnaires were distributed to collect data utilizing non-probability sampling techniques, particularly judgmental sampling. One hundred responders are needed. The author measures the existing variables using an interval scale. It was discovered that performance expectancy positively influences the intention to utilize the wallet application based on the data processing outcomes. On the other hand, effort expectancy has no discernible impact on intention to use, indicating that users' intentions are unaffected by their expectations regarding the degree of difficulty associated with utilizing the application. Furthermore, it was discovered that effort expectancy positively impacts performance expectancy. It was also found that social influence variables positively impacted use intention. Facilitating conditions did not, however, appear to affect the intention to use significantly